Homoseksual Kaum Santri di Pesantren: (Antara Patologi Sosial dan Perilaku Abnormal) - Azam Syukur Rahmatullah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
This paper discussed about homosexuality of santri in Pesantren.. In reality based on the results of the study, in Pesantren there are deviant behaviours that nganeh-nganehi which is condected by santri. Some behaviours that nganeh-nganehi, are; first, adik-adikan, between senior santri to the yunior santri. Second, mojok done by two santri. Third, kobel, pinching cheeks to yunior santri because have good body. Fourth, tidur kelon, that behaviour mean that santri hughing other santri. Some of these behaviour if left unckhed without handling can cause disease because it is a form of social pathology and abnormal behaviour. Therefore the pesantren ideally have begun to understand homosexuality behaviour of santri that which can growth to other santri.